Investigation of the dielectric relaxation processes in PbZr0.65Ti0.35O3-BaFe12O19 multiferroic ceramic composites - Guerra, J. D. S.; Silva, A. C. [UNESP]; M'Peko, J-C; Hernandes, A. C.; Guo, R.; Bhalla, A. S. (Elsevier B.V., 2014)
The dielectric relaxation processes have been investigated in multiferroic ceramic composites based on the ferroelectric PbZr0.65Ti0.35O3 (PZT) and ferrimagnetic BaFe12O19 (BaM) systems. The frequency dispersion of the complex dielectric permittivity was analyzed over wide frequency and temperature ranges, and the effect of BaM content is depicted. The activation energies for the relaxation processes were also obtained for all the studied compositions and the results suggest the oxygen vacancies-related hopping mechanism to be responsible for the observed behaviors in the studied composites. Furthermore, an anomalous behavior in the activation energy has been observed with the increase of the BaM concentration. The obtained results are discussed within the framework of current models reported in the literature for dielectric relaxation processes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Ferroelectricity; Dielectric properties